A theoretical framework for trust-based news recommender systems and its implementation using defeasible argumentation - Briguez, Cristian Emanuel (2013)
Although the importance of trust in recommender systems is widely recognized, the actual mechanisms of trust propagation and trust preservation are poorly understood. This is partly due to the fact that trust is a complex notion, which is typically context dependent, subjective, dynamic and not always transitive or symmetrical. This paper presents a theoretical analysis of the notion of trust in news recommendation and discusses the advantages of modeling this notion using Defeasible Logic Programming, a general-purpose defeasible argumentation formalism based on logic programming. In the proposed framework, users can express explicit trust statements on news reports, news sources and other users. Trust is then modeled and propagated using a dialectical process supported by a Defeasible Logic Programming interpreter. A set of basic postulates for trust and their representation by means of defeasible rules is presented. The suitability of the approach is investigated with a set of illustrative examples and then analyzed from a formal perspective. The obtained results indicate that the proposed framework provides a solid foundation for building trust-based news recommendation services.